Evaluating the impact of the violence prevention and handling team (TPPK) in reducing bullying and violence in high schools - Suhendri, Suhendri; Widiharto, Chr. Argo; Prasetyo, Agung; Setiawan, Agus (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study is based on cases of violence in schools which include cases of bullying that still often occur. To overcome violence in schools, the government issued Permendikbudristek number 46 of 2023 concerning the handling of acts of violence in schools. In this regulation, the government requires every school to form a Violence Prevention and Handling Team (TPPK) to reduce the increasing cases of violence in schools. The problem is that since this regulation was issued on August 4, 2023 until February 2024, only 79.39% of schools have formed it. On the other hand, cases of violence in schools still often occur today. The purpose of this study is to determine the correlation between TPPK that has been formed in schools and acts of violence and bullying behavior. The research method used is quantitative correlation to determine the relationship between variables involving three research variables, namely the TPPK variable, the school violence variable and the bullying behavior variable. The population of this study was 1,527 high school students in Semarang who had experienced violence at school or who had been victims of bullying. The sampling technique used was a simple random sampling. The sample of this research was 248 students from 9 public high schools and 10 private high schools in Semarang. Data analysis used the Mann Whitney U Test and simple linear regression supported by IBM SPSS Statistics 25 from Windows software. The results of the study showed that the formation of TPPK was able to minimize acts of violence and bullying behavior in schools. However, the acts of violence and bullying behavior that occurred did not show significant differences in results, both in schools that had formed TPPK and those that had not. These results indicate that the TPPK that has been formed in schools is not fully effective even though it has influenced violent behavior in schools. For this reason, the role of TPPK members still needs to be improved by providing skills training in preventing and handling violence in schools.